Burned, banished or burnished a pilot study of a school reintegration programme - Horwitz, Ula Nadine (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
It is the aim of this research to create a manual and programme for the reintegration of burn-injured primary-school learners in order to assist in their re-socialisation, and to act as a buffer against depression, conduct disorders, and academic lag. Additional aims of the programme included being resource-efficient, flexible, and compatible with Outcomes-Based Education (aBE) principles evidenced in Curriculum 2005. The final aim of the research involved designing the programme in order for teachers to be able to facilitate it. The manual and programme were evaluated through an embedded case study, encompassing a mildly disfigured burn-injured learner, his family, and his school environment by way of his class and teacher. The programme was found to be efficient in its use of resources, congruent with aBE principles, and engaging of the learners and teacher. Participation in the intervention seemed to afford the burn-injured learner with a buffer against depression, but did not prevent academic lag. Minimal teasing was encountered after the programme was implemented, which is contrary to the expected outcomes based on the literature available. Teacher facilitation was not achieved, however, numerous benefits were derived from the intervention for the majority of the participants.
Keywords: Learning disabled children; Burns and scalds in children; Learning disabled children -- Education -- Curricula; Learning disabled children -- Psychological aspects; Learning disabled children -- Physiological aspects